THE RELATIONSHIP BETWEEN MANGROVE DENSITY AND SEDIMENTATION RATE IN COASTAL KUALA JAMBI DISTRICT TANJUNG JABUNG TIMUR JAMBI PROVINCE - Chaniago, Rizki; Samiaji, Joko; Wibowo, Muhammad Arief (Asian Journal of Aquatic Sciences, 2023)
This research was carried out from March to April 2021 in the coastal area of ​​Kuala Jambi District, Tanjung Jabung Timur Regency, Jambi Province. The samples were processed at the Marine Biology and Marine Chemistry Laboratory, Faculty of Fisheries and Marine, Universitas Riau, which aims to examine the density of mangroves, analyze the sedimentation rate, and know the relationship between mangrove density and sedimentation rate. A survey method was used in this study. The results showed that the dominant mangrove species in the coastal waters of Kuala Jambi was Sonneratia alba with an Important Index Value (INP) of 103.5%. Mangrove density in the coastal waters of Kuala Jambi was included in good criteria with moderate and very dense mangrove cover. The bottom sediment of the coastal waters of Kuala Jambi was dominated by the type of sandy mud with a percentage of 42.23 - 55.63%. The value of the sedimentation rate in the coastal waters of Kuala Jambi at station I ranged from 94.401 to 141.602 mm/year. At station II, the sedimentation rate was between 98.692 and 168.778 mm/year, while at station III the sedimentation rate was from 100.122 to 145.893 mm/year. Mangrove density had a very close relationship with the sedimentation rate, where the higher the mangrove density, was followed by the higher the sedimentation rate.